2020
DOI: 10.1016/j.jiec.2019.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Application of a novel approach to modelling the supercritical extraction kinetics of oil from two sets of chia seeds

Abstract: A B S T R A C TThe kinetics of the supercritical fluid extraction of edible and discarded chia seeds was studied and modelled for the first time. The total oil was removed at 45 MPa and 60 C after 240 min. The extraction kinetics was simulated using a dynamic model in gPROMS ModelBuilder environment and the kinetic parameters estimated. Triolein was chosen as a model compound of the chia oil. The agreement between the experimental yields and those calculated by the model was good with deviations in the range (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Also, ScCO2 extraction of BFRs was proved to be of various degrees of success in extraction efficiency with or without co-solvents, although the solvation power of ScCO2 is generally limited towards polar or high molecular weight compounds Suzuki et al, 2002;Altwaiq et al, 2003). Otherwise, extraction kinetics must be investigated to validate process scale-up and develop successful industrial processes (Nimet et al, 2011;Sodeifian et al, 2016;Villanueva-Bermejo et al, 2020). Despite this, to our knowledge, there have only been few such studies reported previously, either off-line or on-line, for BFR extraction (Bunte et al, 1996;Wang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Also, ScCO2 extraction of BFRs was proved to be of various degrees of success in extraction efficiency with or without co-solvents, although the solvation power of ScCO2 is generally limited towards polar or high molecular weight compounds Suzuki et al, 2002;Altwaiq et al, 2003). Otherwise, extraction kinetics must be investigated to validate process scale-up and develop successful industrial processes (Nimet et al, 2011;Sodeifian et al, 2016;Villanueva-Bermejo et al, 2020). Despite this, to our knowledge, there have only been few such studies reported previously, either off-line or on-line, for BFR extraction (Bunte et al, 1996;Wang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%